SCREENING SOME GRAIN SORGHUM (Sorghum bicolor L. Moench) GENOTYPES FOR GRAIN YIELD AND PLANT TOLERANCE AGAINST SPOTTED STEM BORER Chilo partellus (Swinhoe) - A. M, Ashwag.; Zayed, Mawahib. M. F.; Kheir, Saif eldin. M.; Elsadig, Atif. I. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
An experiment was conducted under irrigation at Experimental Farm of the College of Agricultural Studies, Sudan University of Science and Technology, Shambat in Khartoum State, Sudan for two cropping seasons (Autumn and Winter) during 2016/2017. the objectives were to screen the relative resistance / susceptibility of 22 genotypes of sorghum against stem borer (Chilo partellus), and for yield and its components. The plants were subjected to natural infestation by spotted stem borer. Three resistance expressing traits, i.e. percentage of infested plants(IP), percentage of plants with dead heart effect (DH) and intensity of damage (ID), Growth and grain yield traits were measured. Results showed that, genotype G.1.1.4 was found to be the most resistant with respect to all the damage types studied. The highest yielding genotypes in Autumn Were G.1.1.4(1.37t/ha), G.1.1.16(1.36t/ha) and F-3 (1.31t/ha). G.1.1.4 was a high yielding stable variety throughout the two seasons. In addition, the genotypes (G.1.1.16, F-3, Tabat and F-10) have relatively good level of resistance to infestation by stem borer (Chilo partellus). The genotypes gave higher yields in Autumn than in Winter probably due to the favorable environmental conditions of the rainy season and the lighter infestation by the stem borer. These genotypes might be considered potentially resistant varieties and may serve as material of interest in sorghum improvement programme.